Understanding Draupadi as a paragon of gender and resistance - Motswapong, Pulane Elizabeth (Stellenbosch Theological Journal, 2017)
In this article Draupadi will be presented not only as an unsung heroine in the Hindu epic Mahabharata but also as a paragon of gender and resistance in the wake of the injustices meted out on her. It is her ability to overcome adversity in a venerable manner that sets her apart from other women. As a result Draupadi becomes the most complex and controversial female character in the Hindu literature. On the one hand she could be womanly, compassionate and generous and on the other, she could wreak havoc on those who wronged her. She was never ready to compromise on either her rights as a daughter-in-law or even on the rights of the Pandavas, and remained ever ready to fight back or avenge with high handedness any injustices meted out to her. She can be termed a pioneer of feminism. The subversion theory will be employed to further the argument of the article. This article, will further illustrate how Draupadi in the midst of suffering managed to overcome the predicaments she faced and continue to strive where most women would have given up.